Current research and challenges in modelling wear, friction, and noise in mechanical contacts - Kalifa, Mohamed; Starr, Andrew; Khan, Muhammad (Sage, 2025)
In recent years, the investigation of friction noise which using to predict the wear has gained increasing attention within the field of tribology. In a wide variety of industries, the wear of mechanical components is a matter of major concern, as it directly affects the working life of machinery and equipment such as brake systems and high-speed running machines. Numerous earlier studies, using mathematical, analytical, and finite element methods (FEM), have proposed various hypotheses concerning contact dynamics and friction surface characteristics with the goal of modeling the contact mechanisms. Modelling mechanical contact with rough surfaces poses significant challenges. This study emphasizes the need for advanced modelling techniques by revealing the limitations of existing models in accurately predicting wear, friction, and frictional noise. The analysis highlights the importance of linking friction, wear, and noise in both dry and lubricated conditions, and underscores the necessity of addressing current gaps to develop more precise wear prediction methods based on noise generation in industrial applications. This paper is to review prominent existing models, exploring their approaches to noise generation from friction and its subsequent effect on surface wear. The paper aims to identify key limitations and challenges in accurately modelling these interdependencies. While previous research has often focused on wear caused by friction between surfaces, there is a notable gap in understanding the relationships between frictional noise, friction coefficient, surface roughness, and wear under sliding contact. Current models still face limitations, such as the influence of lubricants.
Keywords: Wear; friction; noise; mechanical contacts; modelling; surface roughness; lubrication regimes; asperity interactions; monitoring process; noise generation; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4017 Mechanical engineering